Pump power optimization for linear cavity multiwavelength Brillouin-Raman fiber laser - Abass A.K.; Jamaludin M.Z.; Al-Mansoori M.H.; Abdullah F.; Al-Mashhadani T.F.; Ali M.H. (Elsevier GmbH, 2023)
Brillouin scattering; Dispersion compensation; Fiber lasers; Fibers; Nonlinear optics; Signal to noise ratio; Tuning; Brillouin Stokes; Dispersion compensating fibers; Linear cavity; Multi wavelength fiber laser; Multiwavelength; Optical signal to noise ratio; Raman fiber lasers; Wide tuning range; Pumping (laser)